The economic and social effects of the Economic Partnership Agreements on selected African countries - Jan Grumiller; Werner G. Raza; Cornelia Staritz; Bernhard Tröster; Rudi von Arnim (Austrian Foundation for Development Research (ÖFSE), 2018)
The European Union (EU) has concluded or currently is in the process of concluding Economic Partnership Agreements (EPAs) with the group of African, Caribbean and Pacific (ACP) countries. Instead of the unilateral approach prevalent until the Lomé Agreements, the EPAs are bi-regional reciprocal agreements, which commit both parties. Unsurprisingly, the negotiations on the EPAs have thus proofed challenging and highly controversial. Given their political sensitivity, the EPAs must deliver tangible benefits to the African partners. Thus, the trade liberalization and further changes facilitated by the agreements must trigger sustainable economic development for the African partner countries, i.e. economic growth that is socially inclusive and respects ecological boundaries. EPAs are therefore primarily to be judged against this yardstick, which is the approach adopted in this study. Apart from assessing the impact of the EPAs and investigating export potentials, the study also aims at providing policy recommendations for EU Development Cooperation in the latter's efforts to support development-friendly implementation of the EPAs. The report starts with an assessment of the main provisions of the three EPAs covered - the South African Development Community EPA (SADC-EPA), the Economic Community of West African States EPA (ECOWAS-EPA) and the East African Community EPA (EAC-EPA), thereby focusing on the market access offer and the provisions in the agreement which potentially limit the developmental policy space as well as offer a potential to strengthen sustainability aspects in African partner countries. Then the implications of the three specific EPAs with a focus on Mozambique, Ghana and Uganda, respectively, are scrutinized. The respective analyses provide assessments of the economic impact of the three regional EPAs on Mozambique, Ghana and Uganda, based on simulations with the ÖFSE Global Trade Model. Based on interviews with stakeholders during field research in the three countries, implementation challenges associated with the agreements are discussed. Further, different sectoral case studies are analyzed to investigate the potential of the EPAs on the export side, highlighting the opportunities and challenges for export promotion policies in the context of global value chains and related lead firm strategies as well as local competitiveness conditions. The five sectoral case studies include the cotton, textile and apparel sectors in selected SADC countries with a focus on Mozambique, the cocoa and mango sectors in Ghana, and the coffee and fish sectors in Uganda.
Additional information: Final report, 12 July 2018
Keywords: 330